A Novel Watermarking Algorithm based on SURF and SVD - Wei Wang; Wenhui Li; Chengxi Wang; Huijie Xin (Institute of Advanced Engineering and Science, 2013)
Protection against geometric distortions and common image processing operations becomes a much challenging task in image watermarking. To achieve this, a novel watermarking algorithm based on Speeded Up Robust Features (SURF) and Singular Value Decomposition (SVD) was presented for digital image copyright protection. By introducing the SURF’s key points matching and geometric distortion estimation, the attacked watermarked image could be corrected and the watermark synchronization was realized. In this way, the feature regions of the host image, which were used for information hiding, could be correctly detected by the improved Harris-Laplace corner detector even after signal processing and geometric attacks. Finally, the watermark information were embedded into the U matrix of SVD of the host image. The application of the proposed scheme makes the watermark capable of transparent hiding. Extensive experimental results demonstrate that our technique performs better than traditional methods under different attacks. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2305